Pupuk kompos sebagai solusi alternatif mengatasi masalah sampah sisa makanan di pondok pesantren as-sa’adah - Nurullaika, Nurullaika (Maliki Interdisciplinary Journal, 2025)
In 2021, Indonesia is ranked second in waste production in the world. This is especially true for food waste. Indonesia produces a large amount of waste, which is as much as 13 tons per year from various sectors. One of the largest contributing sectors is the household sector, including boarding schools. Islamic boarding schools are also one of the household sectors that produce a fairly large amount of food waste. food waste such as vegetables, fruits, and so on can be useful in the process of making compost. Therefore, researchers conducted research on processing food waste into compost fertilizer at As-Sa’adah Islamic Boarding School as an alternative solution to overcome the problem of food waste. Data collection in this study through semi-structured interviews continued on the demonstration of making compost fertilizer. The compost fertilizer produced from this research is classified as good because after the mustard planting experiment, the mustard grows well. The results of this research are expected to be an alternative solution to the problem of food waste.